1996
DOI: 10.1038/bjc.1996.513
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the androgen receptor and an androgen-responsive protein, apolipoprotein D, in human breast cancer

Abstract: Summary Little is known regarding the activity and function of the androgen receptor (AR) in human breast cancer. In the present study AR was evaluated in untreated primary breast cancers using antisera to the aminoand carboxy-termini of the receptor and quantitated using colour video image analysis. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 29 publications
(21 reference statements)
3
38
1
Order By: Relevance
“…AR was detected followinmg microwave retrieval. as reported previously (Hall et al 1996 Figure 1B). Immunoreactive PSA was also localized in the cytoplasm of tumour cells ( Figure IC) and was present extracellularly in ductal luminae.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…AR was detected followinmg microwave retrieval. as reported previously (Hall et al 1996 Figure 1B). Immunoreactive PSA was also localized in the cytoplasm of tumour cells ( Figure IC) and was present extracellularly in ductal luminae.…”
supporting
confidence: 88%
“…Immunohistochemical studies have demonstrated that at least 801% of primary breast cancers contain AR-positive tumour cells (Kuenen-Boumeester et al 1992: Isola. 1993: Hall et al 1996. Moreover.…”
mentioning
confidence: 98%
“…Androgen signaling may also activate estrogen-responsive genes (3,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). ER-negative and/or PR-negative breast cancers represent f30% of all breast cancers and are known to have a more aggressive clinical course, partly because these tumors are more likely to be poorly differentiated and of higher histologic grade (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Androgen receptor (AR) is expressed in normal mammary epithelial and stromal cells [124;125]. Many pathologic studies have also demonstrated that over 70% of human breast cancer biopsies from untreated women are positive for AR; the ercentages are usually higher than, or equal high to, the percentages of ER and PR positivity [126][127][128][129][130][131][132][133][134][135]. These facts provide the basis for a direct AR-mediated action of androgens in the normal and malignant breast tissues.…”
Section: Uses Of Androgens In Womenmentioning
confidence: 99%